Efecto de la temperatura sobre el crecimiento de plantas de papa (Solanum tuberosum L.), variedades atlantic 1625 frito lay, crecidas in vitro - Orozco, Rafael (2000)
The effect of two temperature cycles (30/26 °C and 27/25 °C, day/night) on the growth of two varieties of potato plants (1625 Frito Lay and Atlantic) was studied. Plants were grown in MS (1962) cultivation medium (Gibco Laboratories) at a concentration of 17 g/L, supplemented with vitamins and aminoacids. In both varieties the high temperature (30/26 °C) caused a decreased in stem diameter and in number of nodes per plant, as well as an increment in the internodal length and in overall plant height. On the other hand, the higher temperature decreased significantly (P < 0,05) the root length in the Frito Lay variety while the Atlantic variety showed a non significant increase.